2019
DOI: 10.3390/su11226323
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intelligence Approach of a Sequential Minimal Optimization-Based Support Vector Machine for Landslide Susceptibility Mapping

Abstract: The main objective of this study is to propose a novel hybrid model of a sequential minimal optimization and support vector machine (SMOSVM) for accurate landslide susceptibility mapping. For this task, one of the landslide prone areas of Vietnam, the Mu Cang Chai District located in Yen Bai Province was selected. In total, 248 landslide locations and 15 landslide-affecting factors were selected for landslide modeling and analysis. Predictive capability of SMOSVM was evaluated and compared with other landslide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…Validation performance is a critical step in a modeling procedure, for which several statistical indices has been suggested and used [13,14,[49][50][51][52]. In this study, we used Area Under Receiver Operating Characteristic (ROC) curve (AUC) [39,[53][54][55][56], Root Mean Squared Error (RMSE) [57][58][59][60][61][62][63][64], Kappa, Accuracy (ACC), Specificity (SPF), Sensitivity (SST), Negative predictive value (NPV), and Positive predictive value (PPV) [65][66][67][68][69]. Detail description of these indices is presented in published literature [61,[70][71][72][73][74][75][76][77].…”
Section: Validation Methodsmentioning
confidence: 99%
“…Validation performance is a critical step in a modeling procedure, for which several statistical indices has been suggested and used [13,14,[49][50][51][52]. In this study, we used Area Under Receiver Operating Characteristic (ROC) curve (AUC) [39,[53][54][55][56], Root Mean Squared Error (RMSE) [57][58][59][60][61][62][63][64], Kappa, Accuracy (ACC), Specificity (SPF), Sensitivity (SST), Negative predictive value (NPV), and Positive predictive value (PPV) [65][66][67][68][69]. Detail description of these indices is presented in published literature [61,[70][71][72][73][74][75][76][77].…”
Section: Validation Methodsmentioning
confidence: 99%
“…The area under this curve is called the AUC, and the model with the highest AUC has the highest relative performance [52][53][54][55][56][57][58][59][60][61]. The AUC values equal to 0.5 indicate random prediction for a model [62][63][64][65][66].…”
Section: Receiver Operating Characteristic (Roc) Curvementioning
confidence: 99%
“…Considering the common process for LSM, these landslide samples are randomly divided into two parts: 304 (70%) samples out of them are used for training and the remaining 130 (30%) samples are retained for the validation of the calibrated susceptibility models (Dou et al 2019;Wang et al 2020). Note that such ratio of training and validating data has been widely used in the literature (Pham et al 2019;Hu et al 2020;Zhao and Chen 2020;Dou et al 2020b) and some internal analyses also found this ratio yield good results.…”
Section: Landslide Inventorymentioning
confidence: 99%